1988
DOI: 10.1007/bf00015662
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of the genomic clone for pathogenesis-related protein 1a from Nicotiana tabacum cv. Xanthi-nc

Abstract: We describe the isolation of the chromosomal gene for pathogenesis-related protein 1a from Nicotiana tabacum. A 2 kb fragment containing the PR-1a gene as well as 5' and 3' flanking DNA has been sequenced and the transcriptional start site has been determined by primer extension and S1 nuclease mapping. 80% of the protein sequence from purified PR-1a and 20% of the sequence of purified PR-1b has also been determined and used to verify the nomenclature established for the PR-1 cDNAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

1989
1989
2000
2000

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 18 publications
1
43
0
Order By: Relevance
“…Samsun NN and Xanthi-nc (data not shown). Subsequently, two independent clones were sequenced in total both containing the same nucleotide sequence identical to the Samsun NN and Xanthi-nc PR-1 a sequences (Cornelissen et al, 1987;Ohshima et al, 1987;Payne et al, 1988). Taken together, these data suggest that there is no nucleotide sequence variation in the 902-bp upstream regions among PR-1 a genes from different tobacco cultivars.…”
Section: Isolation Of the 5'-flanking Region Of The Pr-la Gene From Nmentioning
confidence: 82%
See 2 more Smart Citations
“…Samsun NN and Xanthi-nc (data not shown). Subsequently, two independent clones were sequenced in total both containing the same nucleotide sequence identical to the Samsun NN and Xanthi-nc PR-1 a sequences (Cornelissen et al, 1987;Ohshima et al, 1987;Payne et al, 1988). Taken together, these data suggest that there is no nucleotide sequence variation in the 902-bp upstream regions among PR-1 a genes from different tobacco cultivars.…”
Section: Isolation Of the 5'-flanking Region Of The Pr-la Gene From Nmentioning
confidence: 82%
“…1 A) was added to give plasmid -1533PRla [GUS]. The PR-1 a promoter/ GUS expression cassettes were excised from the respective pUC plasmids as HindIII-EcoRI fragments and ligated into (Cornelissen et al, 1987;Ohshima et al, 1987;Payne et al, 1988), the positions of the primers used in the PCR, the extents of the PCR products obtained, and the position of the previously isolated 1 clone W38/5 (Pfitzner et al, 1988) pBinl9 (Bevan, 1984). The mobilization of chimeric constructs into Agrobacterium and the transformation of tobacco plants have been described previously (Beilmann et al, 1991).…”
Section: Construction and Transformation Of Chimeric Reporter Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…We reported the complete sequence of the PR-1a gene and two PR-1 pseudogenes , two active PR-S genes (Van Kan et al, 1989), and two genes encoding a glycine-rich protein (GRP) that does not show homology to any of the known PR proteins . In addition, the sequence of the PR-1a gene was reported by severa1 other groups (Ohshima et al, 1987;Payne et al, 1988;Pfitzner et al, 1988). The PR-1a and GRP genes are strongly induced by spraying tobacco with a 5 mM salicylate solution, whereas the PR-S genes are weakly induced by this treatment.…”
Section: Introductionmentioning
confidence: 79%
“…The PR-la messenger transcribed from this gene will contain 28 5'-noncoding nucleotides in front of the start codon and possibly terminate somewhere on one of several polyadenylation signals in the 322-nucleotide-long 3'-noncoding region. Payne et al (1988) found that PR-la mRNA from Xanthi-nc tobacco is polyadenylated at at least two sites in this nontranslated region. If transcription termination of the transgenic messenger takes place at these internal polyadenylation sites, the resulting messenger will be only one nucleotide shorter than the endogenous PR-la messengers.…”
mentioning
confidence: 97%